Perbandingan penampilan fisiologis padi genotipe lokal dan nasional untuk mengatasi kekeringan - Cut Nur Ichsan; Ihsan Gamal; Erida Nurahmi; Gina Erida; Irfan Irfan (Jurnal Floratek, 2015)
Physiologycal Performance Comparison of Rice from Local and National Genotype to Overcome Drought ABSTRACT. Rice (Oryza sativa) is a major food commodity in the world that affected by global warming. It can be seen from crop harvest failure due to drought in many parts of the world. It is necessary to promote Land Race which has adapted to specific conditions, this is to strengthen national seed systems. This study aimed to compare the character of national varieties with local varieties that allow for superior varieties such as Cirata, Inpari 7, Ciherang, IR 64, Situ Patenggang, Situ Bagendid, Limboto and Towuti as a control and compare with 11 local genotypes (Rom Mokot, Pade Mas, Salah Manyang Ru, Bo Santeut, Si Gupai, Si Kuneng, Pade Barcelona, Sanbei, Ramoes, Si Puteh and Si Tandun) were germinated in a solution of PEG 6000 2,5% (25 grams / liter of solution). The results showed that local genotype have characters that can match with the national release varieties in the benchmark vigor reflected in germination rate, simultaneity germination and T50. Local genotype Sitandun, Si Puteh, Ramos, Sanbe, Pade Barcelona, Bo Santeut, Si gupai and Pade Mas reached 50% germination even faster than the national release varieties except Towuti and Limboto. For simultaneity germination, local genotypes Pade barcelona and Sanbe equal to Towuti, Ciherang and Inpari 7. For germination rate, local genotype Pade Mas, Pade Barcelona, Sanbe, Ramos, and Siputeh equal to Towuti, Inpari 7, Ciherang and Situ Patenggang.